The easiest children to reach are most likely to be infected with ocular Chlamydia trachomatis in trachoma endemic areas of Niger. - Abdou Amza; Boubacar Kadri; Baido Nassirou; Sun N Yu; Nicole E Stoller; Satasuk J Bhosai; Zhaoxia Zhou; Charles E McCulloch; Sheila K West; Robin L Bailey; Jeremy D Keenan; Thomas M Lietman; et al. (Public Library of Science (PLoS), 2013)
Control programs for trachoma use mass antibiotic distributions to treat ocular Chlamydia trachomatis in an effort to eliminate this disease worldwide. To determine whether children infected with ocular Chlamydia are more likely to present later for examination than those who are uninfected, we compare the order of presentation for examination of children 0-5 years, and the presence of ocular Chlamydia by PCR in 4 villages in Niger where trachoma is endemic.We conducted a cluster-randomized, controlled trial where 48 randomly selected villages in Niger are divided into 4 study arms of different mass treatment strategies. In a substudy of the main trial, we randomly selected 1 village from each of the 4 study arms (4 total villages) and we evaluated the odds of ocular Chlamydia versus the rank order of presentation for examination and laboratory assessment before treatment was offered.We found the odds of harboring ocular Chlamydia dropped by more than 70% from the first child examined to the last child examined (OR 0.27, 95% CI 0.13-0.59, P = 0.001) in the 4 randomly selected villages. We found the odds of active trachoma dropped by 80% from the first child examined to the last child examined (OR 0.20, 95% CI 0.10-0.4, P<0.0001) in the 48 villages in the main trial.This study demonstrates that even if the WHO recommended 80% treatment coverage is not reached in certain settings, children 0-5 years with the greatest probability of ocular Chlamydia have higher odds of receiving attention because they are the first to present. These results suggest there may be diminishing returns when using scarce resources to track down the last few children in a mass treatment program.ClinicalTrials.gov NCT00792922.